Strategi dan Kendala Kepala Madrasah Dalam Peningkatan Peran Hubungan Masyarakat di MAN 4 Aceh Besar - Mardhiah, Ainul; Sardaniati, Nia (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The strategy of the madrasah principal is an important step in managing and developing the relationship between the school and the community. Public Relations (PR) plays a strategic role in building a positive image of the madrasah and establishing effective communication between the madrasah and its external environment. However, the role of PR has not been fully optimized in many educational institutions. This study aims to identify the strategies employed by the principal of MAN 4 Aceh Besar to enhance the role of PR and to explore the challenges encountered during the process. This research uses a qualitative method with a case study approach. Data collection techniques include observation, interviews, and documentation. The results show that the principal applies integration and intensive strategies, which serve to strengthen communication with parents, disseminate information via social media, manage public opinion, and increase community participation. However, these strategies face challenges such as limited human resources, lack of training, and restricted access to information. Enhancing PR capacity and managerial support is necessary to optimize the PR function. This study suggests that the madrasah principal should continue strengthening strategies to improve the role of PR.